Studi Komparatif Penyaluran Fasilitas Pembiayaan dalam Mendukung Sektor Industri Makanan Halal pada Bank Umum Syariah di Indonesia dan Malaysia - Rizky Nur Muhammad; Alvien Septian Haerisma; Yeni Nurkhasanah (CIEBER: Contemporary Islamic Economic and Business Review, 2025)
This research aims to analyze the comparison of financing facilities, implementation of strategies and policies as well as the differences between each existing financing facility at BSI and BIMB to support the halal food industry. This research uses a comparative qualitative research type with a qualitative approach. The data sources used are secondary data sources via the web from each bank, previous research, annual reports, international journals and several relevant YouTube channels. The results show that the financing facilities distributed by PT Bank Syariah Indonesia Tbk (BSI) to support the halal food industry sector are said to be not optimal because there are no financing facilities aimed directly at supporting the halal food industry sector. Meanwhile, Bank Islam Malaysia Berhad (BIMB) is considered quite optimal because it has financing facilities designed to support the growth of MSMEs in the halal industry, especially the halal food industry sector. Through the various facilities provided by these two sharia banks, it really helps business actors, both MSMEs and companies, especially those operating in the halal food industry, although the financing distributed is aimed at business actors in general.